ECUACIONES LINEALES EN CAMPOS GRAVITATORIOS DEDILES - Villegas Silvaa, Fulgencio (2005)
The movement equations in the General Theory of relativity corresponding to a particle in a weak gravitational field, le us appoint analogy with the movement equations of a charged particle in a electromagnetic field. A study of this solutions let us appoints a deep analogy between gravitation and electromagnetism. As consequence of this result you can express the weak gravitational fields by a system of equations similar to the Maxwell's for the electromagnetism field.